2022
DOI: 10.28991/cej-2022-08-08-010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HDPE Utilization and Addition of Wetfix-Be to Asphalt Pavement in Tropical Climates

Abstract: Plastic Waste (PW) is one of the primary sources of pollution, leading to drainage system blockages, thereby causing floods and road pavement damage. One of the major ways to reduce pollution due to plastic waste and excessive exploitation of natural resources is through the development of HDPE. It is also important to reduce damage to road pavement structures by improving the quality of the asphalt used during construction. Therefore, this research aims to analyze the effects of using HDPE shale, an ecologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 25 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Binder modification with recycled polymer and/or HDPE plastic waste decreases the penetration value and weight loss; increases the viscosity, ductility, flash point temperature, and softening point temperature. This makes the bitumen harder and resistant to high temperatures (Al-Hasan et al 2020 ; Nawir and Mansur 2021 , 2022 )…”
Section: Discussionmentioning
confidence: 99%
“…Binder modification with recycled polymer and/or HDPE plastic waste decreases the penetration value and weight loss; increases the viscosity, ductility, flash point temperature, and softening point temperature. This makes the bitumen harder and resistant to high temperatures (Al-Hasan et al 2020 ; Nawir and Mansur 2021 , 2022 )…”
Section: Discussionmentioning
confidence: 99%
“…Clayey soils are characterized by high consistency (stiff to hard), high expansion, and low bearing capacity [1]. Therefore, stabilizing GF soils has been the subject of several studies (e.g., [2][3][4]) by adding stabilizers such as lime and cement, construction waste, and crushed glass. Although research has shown improvement in GF soils through these studies, incorporating recycled asphalt pavement (RAP) residues has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The RAP material combines old petroleum asphalt cement (named "CAP" in Brazil) and aggregate obtained through pavement milling. The properties of milled material depend on the road type, the aggregate used in the mixture, the type of milling machine employed, the exposure time of the pavement to weather conditions, and the CAP content [2]. The cold in-place recycling of pavements is an in-situ technique for the structural and functional rehabilitation of pavements that allows the reuse of the existing pavement structure by adding a stabilizing agent.…”
Section: Introductionmentioning
confidence: 99%
“…Slow removal of water from the bituminous top requires the use of modified bitumen with approximately 15% of polymer dosing or the use of Wetfix Be especially recommended for warmer climates. [2][3] To achieve effective and low-cost sustainable urban drainage system enabling quick removal of storm water which is economical also is a very important question and need of the hour. Permeable pavements are considered to be one of the effective measures for LID (i.e.…”
Section: Introductionmentioning
confidence: 99%